Manusia sebagai Gambar Allah yang Membawa Kuasa Perkataan-Nya - Pujiwati Pujiwati; Imelda Herlina Sitohang; Christofer Cahyadi; Djuwansah Suhendro P Stephanus; Eunike Eunike; Evi Sondang Pangaribuan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
The real man was created in a likeness to God the Creator -who created the universe with the words of his word, so that man could be a representation of god in this world. Yet, from time to time, it has often been a disregard for the power of the words of god that have been placed in his mouth and heart (Deuteronomy 30: 14). Problems arise when man uses his words without understanding of the truth and is not based on an attitude of respect and respect for the divine power embodied in them. The purpose of this study is to describe the effects of humans as bearers of God’s word based on Genesis 1:3.26 as applied in Genesis 2:19 and Numbers 14:22-23. In this study, the methods used are descriptive qualitively with an approach to an understanding and understanding of the God reflected in each human.